Cyborg human and machine communication paradigm - Kaswan, Kuldeep Singh; Dhatterwal, Jagjit Singh; Baliyan, Anupam 1976-; Rani, Shalli (CRC Press, 2023)
This book provides in-depth information about the technical, legal, and policy issues which are raised when humans and artificially intelligent machines are enhanced by technology.
Print version record
Keywords: Cyborgs; Artificial intelligence; Intelligence artificielle; artificial intelligence